Prophet Moses' Self-efficacy in Q.S. Asy-Syu'ara Verses 10-22 and Hadits: A Psychological Analysis Based on Tafsir Ibn Kathir - Ramadhan, Tubagus Naufal; Laily Liddini (Aqwal: Journal of Qur'an and Hadis Studies, 2025)
Background and objectives: The article analyzes the dynamics of Prophet Moses’ self-efficacy when he was commanded to confront Pharaoh as narrated in Q.S. Asy-Syu’ara verses 10–22 and supported by related prophetic traditions, addressing the lack of focused studies that map Moses’ psychological transition from fear and doubt to confident prophetic agency using a contemporary self-efficacy framework. The study aims to reconstruct this process. Method: This article use a qualitative descriptive, library-based method that uses Q.S. Asy-Syu’ara 10–22, Tafsir Ibn Kathir, and two authentic hadiths about Moses’ patience and his advice in the Isra’ Mi‘raj narrative as primary data, complemented by scholarly literature on Albert Bandura’s self-efficacy theory. Main results: Textual units of Moses’ utterances, divine responses, and narrative contexts are coded into Bandura’s dimensions of magnitude, strength, and generality and the four main sources of self-efficacy, revealing an initial phase of low self-efficacy marked by fear of rejection, awareness of verbal limitations, and anxiety over a past killing, which gradually shifts into stable and realistic confidence through divine assurance, the appointment of Aaron, and the experience of miracles. Contribution: The study contributes by integrating Bandura’s self-efficacy model with classical Qur’anic exegesis and hadith, thereby proposing a religious self-efficacy reading of Moses that expands Islamic psychology and Qur’an–Hadith studies beyond purely moralistic narrations. Conclusion: These insights offer a conceptual basis for designing faith-based strategies to strengthen self-efficacy in Islamic education and da‘wah, particularly for individuals who struggle with fear, doubt, and perceived inadequacy in carrying out religious and social responsibilities.